A Review of the Clinical Utility of the Distress Thermometer (International Journal of Innovative Research in Computer Science & Technology, 2021)
The Discomfort Thermometer (DT) is a  well-established screening tool that is both sensitive and  specific to the concept of cancer distress. Its shortness  makes it suitable for integrating into a distress  management system. A literature study was conducted to  determine how far this concept has progressed in practice  and to assist future research. The following databases  were systematically searched: Pubmed, CINAHL,  PsycINFO, Ebsco, ASSIA, British Nurses Directory,  AMED, CCTR, and HMIC are just a few of the databases  available. In forty studies, the DT's function was explored  alone, in conjunction using the issue list (PL), and/or  other approved indicators. In order to demonstrate  ‘cosiness' in these groups and identify variables  associated with distress, the bulk of research validated the  DT against other strong measures of distress. Almost all  of the studies suggested that their results be tested in  clinical practice in the future. A tiny part of the literature  looked at the DT's clinical usefulness as a consultation  facilitator and found it to be promising in this respect. It  is determined that there is sufficient validation evidence,  and future study should concentrate on the usefulness of  DT as part of a systematic distress treatment centre, as  recommended by the majority among these  investigations.
Keywords: Distress; Cancer; Management; Oncology; Thermometer